Usefulness of two instruments in assessing depression among elderly Mexicans in population studies and for primary care Utilidad de dos instrumentos para valorar depresión entre adultos mayores de México en estudios poblacionales y para la atención en el primer nivel de salud - Sergio Sánchez-García; Teresa Juárez-Cedillo; José Juan García-González; Claudia Espinel-Bermúdez; Joseph J Gallo; Fernando A Wagner; Felipe Vázquez-Estupiñán; Carmen García-Peña (Instituto Nacional de Salud Pública, 2008)
OBJECTIVE: To determine the psychometric qualities of the CES-DR and GDS scales in the elderly and compare them to clinical psychiatric diagnoses. MATERIAL AND METHODS: The first phase consisted of home interviews for determining the psychometric qualities of the GDS and CES-DR scales. In the second phase, psychiatrists conducted diagnostic interviews. The sample consisted of 534 participants older than 60 years of age insured by the Mexican Institute of Social Security. RESULTS: First phase: Cronbach's alpha for the GDS was 0.87 and 0.86 for CES-DR. The GDS factorial analysis found eight factors that could explain 53.5% of the total variance and nine factors that explained 57.9% in the CES-DR. Second phase: Compared to the psychiatric diagnoses, CES-DR reported a sensitivity of 82% and a specificity of 49.2%; GDS reported 53.8% sensitivity and 78.9% specificity. CONCLUSIONS: CES-DR and GDS scales have high reliability and adequate validity but the CES-DR reports higher sensitivity. RESUMEN OBJETIVO: Determinar las propiedades psicométricas de las escalas CES-DR y GDS para depresión en población anciana y compararlas con el diagnóstico clínico psiquiátrico. MATERIAL Y MÉTODOS: La primera fase consistió en entrevistas en casa para determinar las propiedades psicométricas. En la segunda fase, los psiquiatras condujeron entrevistas diagnósticas. La muestra consistió en 534 participantes de 60 años y más asegurados por el Instituto Mexicano del Seguro Social. RESULTADOS: Primera fase: Alfa de Cronbach para el GDS y CES-DR fue de 0.87 y 0.86, respectivamente. El análisis factorial del GDS reportó ocho factores que explicaron 53.5% de la varianza, comparado con nueve del CESDR que explicaron 57.9%. Segunda fase: Comparado con el diagnóstico psiquiátrico, el CES-DR reportó una sensibilidad de 82% y una especificidad de 49.2% comparado con 53.8% y 78.9%, respectivamente del GDS. CONCLUSIONES: Las escalas CES-DR y GDS tienen consistencia y adecuada validez pero el CES-DR reporta más alta sensibilidad.